The Turn to Virtue in Climate Ethics: Wickedness and Goodness in the Anthropocene - Jenkins, Willis (Environmental ethics, 2016)
Ethicists regularly turn to virtue in order to negotiate features of climate change that seem to overwhelm moral agency. Appeals to virtue in climate ethics differ by how they connect individual flourishing with collective responsibilities and by how they interpret Anthropocene relations. Differences between accounts of climate virtue help critique proposals to reframe global ecological problems in terms of resilience and planetary stewardship, the intelligibility of which depends on connecting what would be good for the species with what would be good for an individual life. A pragmatic way of establishing that connection may need a strong role for respect of nature.